The Future of Public Employee Unionism in the United States - Stieber, Jack (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
The author makes an evaluation of the significant features of collective bargaining in the United States' public sector. He deals successively with the forms of organization of public employee unionism, the impact of legislation on employee organization, the rivalries existing between various unions, associations, and professional organizations and also with more specific issues such as: the status of supervisors, union security, the strike, political activity and minority participation.